Kurikulum Merdeka Belajar dan Pendidikan Moral Orientasi PAI Pada Madrasah Aliyah Sanana - Umasugi, Hamzah Umasugi, M.Pd.I (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
In the world of education, there is always improvement in the curriculum, now suddenly the curriculum has been introduced as a test subject. The implementation of the independent education curriculum in Madrasah does not include efforts to develop the character or morality of the students, it is done with the aim of creating a culture of worldly knowledge, criticism, innovation and religious philosophy till date. In this part of the article, the author will prepare a way to implement the independent teaching curriculum for improving the moral education in Madrasah Aliyaah Sanana, independent teaching curriculum in Madrasah Aliyah Sanana, will discuss the problem of practicing moral education and Islamic religious education. Makes an effort to make. How can moral education be integrated into Islamic religious education in Madrasah Aliyah Sanana, and what are the methods used to implement the free teaching curriculum to establish moral values ​​in Islamic religious education. The form of research used is to describe the objective of the Independent educational curriculum and the implementation of moral education, and then to clarify the meaning of Islamic religious education. The conclusion that can be drawn is that the present independent curriculum implemented in the form of an educational design pattern in Madrasah is capable of developing individual character on the basis of self-respect and highlighting local cultural values. The focus is on designing the educational landscape. As a step in academic exploration, the nature of projects is more abstract and broader.